Karakterisasi Enzim Nitril Hidratase dan Amidase dari Pseudomonas sp. BP3 dalam Biokonversi Adiponitril menjadi Asam Adipat - Sunarko, Bambang; Sulistinah, Nunik (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTCharacterization of Nitrile Hydratase and Amidase of Pseudomonas sp BP3 in Bioconversionof Adiponitrile to Adipic Acid. Adipic acid is a commercially important compound, primarilyused as precursor for the production of nylon 6.6. It is also used for plasticizer, fibers, and foodadditive. Synthesis of adipic acid by chemical means requires large amount of energy andconcentrated acid. It also produces N2O as by product, which is very toxic and suspectedcauses depletion of the ozone layer. The purpose of this research was to study thebioconversion of adiponitrile by Pseudomonas sp. BP3 and to characterize the involved enzymesin the whole cell. Pseudomonas sp. BP3 was able to utilize adiponitrile as the sole source ofcarbon and nitrogen. Itâs doubling time (td) and growth rate constant (?) during the growth inadiponitrile were 2 hours and 0.346/h, respectively. The optimum pH and temperature of nitrilehydratasewere pH 7.0 and 30Â°C, respectively, while those of amidase were pH 6 and 50Â°C.Vmax and Ks of nitrile hydratase were 8.3 nM/ml.min. and 55.56 mM, respectively, and ofamidase were 5,9 nM/ml.min and 50 mM. The rate of adiponitrile consumption was 0.245 mM/h and of adipic acid formation was 0.181 mM/h. The yield of bioconversion of adiponitrile andadipamide were about 50 % and 25%, respectively.Key words: Bioconversion, adiponitrile, adipic acid, Pseudomonas sp. BP3, nitrile hydratase,amidase